Large scale Rhodian sculpture of Hellenistic and Roman times - Bairamē, Kalliopē, (Access archaeology., 2017)
This volume presents the large-scale Rhodian sculpture of the Hellenistic and Roman period through the publication of 60 unpublished sculptures of life size or larger than life size, together with 45 sculptures already published.